Eksistensi Peradilan Tata Usaha Negara dalam Penggunaan E-Court sebagai Upaya Tata Kelola Pemerintahan yang Baik - Niken Savitri Ramadhani (Jurnal Hukum Lex Generalis, 2022)
Good governance is carried out by updating technology and alternatives related to the service system in the community. One alternative form of management is by making new changes related to electronic justice (E-Court). In this case, the E-Court system applies transparency in the implementation of policies related to the cost of a case. This study aims to determine the existence of the E-Court system in accordance with the principles of good governance. From this problem, observations were made related to the existence of the system (E-Court) in the State Administrative Court. There are still many people who are not familiar with the electronic system, causing the E-Court system not to run well.